Using Offerings to Attract More Customers and Maximize the Sales of Victory Store - Theresia Surya Pratami (Institute of Research and Community Outreach - Petra Christian University, 2022)
Victory Fotokopi/ATK store is a store that provides both services such as photocopy, print, laminating, scan and book binding (Jilid) and products such as stationary, office equipment and birthday supplies. The main problem of Victory store is it does not have any uniqueness or value that makes it different from other stores. Therefore, offerings such as volume discount and bundling are used in this project. A digital poster also used to distribute the offerings through WhatsApp Business to the customers. In conducting the project, I used the theories of four main subjects: brand awareness, marketing, promotion and unique selling point. Also, nine sub subjects: brand advertising, logo, blue, red and yellow colors, digital poster, banner, social media marketing, WhatsApp, offering in marketing, volume discount and bundling. Basically, as the main purpose is to maximize the sales, offerings will be the best solution where it could attract the customers to come and shop more often to the Victory store. Keywords: Brand and Brand Awareness, Brand Advertising, Marketing, Social Media Marketing, Offering in Marketing, Volume Discount, Bundling, Digital poster and Unique Selling Point